Dari Regulasi ke Realita: Tantangan Perlindungan Pekerja Perempuan Shift Malam dalam Perspektif Hak atas Pekerjaan yang Layak - Maya Ermawati; Ucuk Agiyanto (Lembaga Teewan Journal Solutions, 2026)
Women's participation in formal employment, including night shifts, continues to rise amid Indonesia's economic and social changes. However, despite their significant contributions, female night shift workers face unique risks and vulnerabilities often overlooked. Although legal frameworks such as Law No. 13 of 2003 and Ministerial Decree No. 224 of 2003 were designed to provide protection, a wide gap persists between legal mandates and actual workplace realities. This study examines the legal protection arrangements for female night shift workers from the perspective of the right to decent work and analyzes the challenges in their implementation. Employing a normative juridical method with statutory, conceptual, analytical, and comparative approaches, this research finds that while national regulations align with decent work principles and international human rights standards, enforcement remains far from ideal. Many female workers continue to struggle with double vulnerability—as workers and as women—rendering them more susceptible to sexual violence, health issues, and work-family conflicts. This implementation gap reflects the state's incomplete fulfillment of its obligation to respect, protect, and fulfill the right to decent work. Consequently, optimizing protection for female night shift workers necessitates a comprehensive approach encompassing regulatory refinement, strengthened law enforcement, increased awareness, expanded access to justice, and sustained multi-stakeholder social dialogue..